Musculoskeletal disorders and quality of life of dentists - Saliba,Tânia Adas (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: Quality of life has always been a human concern, especially nowadays when job market requirements are exposing dentists to stressing situations and adverse conditions, thus favoring the installation of several labor-related diseases. This study aimed at evaluating labor-related musculoskeletal disorders, painful symptoms and their relation with quality of life and the use of preventive measures by dentists. METHODS: Study population was made up of dentists of the private network (n=64). Two self-applicable questionnaires were used being one to measure quality of life World Health Organization Quality of Life-bref and the other for musculoskeletal disorders. RESULTS: Pain was more prevalent on neck and cervical spine (49.2%), followed by lumbar region (40%). With regard to quality of life, physical domain had higher mean scores (76.5%) followed by social relations domain (74.9%). CONCLUSION: The region with higher prevalence of pain was neck and cervical spine and professionals with pain were not so happy with their quality of life.